Keeping It Halal : The Everyday Lives of Muslim American Teenage Boys - O'Brien, John (John Hoffman), 1973- (Book collections on Project MUSE., 2017)
A compelling portrait of a group of boys as they navigate the complexities of being both American teenagers and good Muslims. This book provides a uniquely personal look at the social worlds of a group of young male friends as they navigate the complexities of growing up Muslim in America. Drawing on three and a half years of intensive fieldwork in and around a large urban mosque, John O'Brien offers a compelling portrait of typical Muslim American teenage boys concerned with typical teenage issues--girlfriends, school, parents, being cool--yet who are also expected to be good, practicing Muslims who don't date before marriage, who avoid vulgar popular culture, and who never miss their prayers. Many Americans unfamiliar with Islam or Muslims see young men like these as potential ISIS recruits. But neither militant Islamism nor Islamophobia is the main concern of these boys, who are focused instead on juggling the competing cultural demands that frame their everyday lives. O'Brien illuminates how they work together to manage their "culturally contested lives" through subtle and innovative strategies--such as listening to profane hip-hop music in acceptably "Islamic" ways, professing individualism to cast their participation in communal religious obligations as more acceptably American, dating young Muslim women in ambiguous ways that intentionally complicate adjudications of Islamic permissibility, and presenting a "low-key Islam" in public in order to project a Muslim identity without drawing unwanted attention. Closely following these boys as they move through their teen years together, Keeping It Halal sheds light on their strategic efforts to manage their day-to-day cultural dilemmas as they devise novel and dynamic modes of Muslim American identity in a new and changing America.